Parrots and Paragrams: AI Language Models and Erasure Poetry. - Middleton, Peter (Modern Philology, 2024)
This essay on poetry and computation borrows a provocative trope from an essay written by AI specialists who describe large language models as "stochastic parrots," copyists relying on probability statistics to generate answers. The history of poetry affords us many instances of textual borrowing that might provocatively be called parroting, repetition embedded in procedural selection from a source text, most recently in the minor genre of erasure poetry. This essay pursues analogies and differences between the digital systems and erasure poetics with the assistance of a poetic device known as the paragram, associated with eccentric searchers for hidden or occult messages in literary classics, as well as linguistic theorists such as Ferdinand de Saussure, Roman Jakobson, and Julia Kristeva. The essay centers on a prominent erasure poem, Voyager (2010) by Srikanth Reddy, and also discusses more briefly texts by Tom Phillips, Ronald Johnson, Janet Holmes, and Susan Howe.